2020
DOI: 10.3389/fpubh.2020.00049
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact and Social Value of Interventions, Services, and Policies: A Methodological Discussion of Health Impact Assessment and Social Return on Investment Methodologies

Abstract: Conclusion: HIA and SROI have many synergies in their approaches. This research suggests potential benefits when used in tandem, or combining the methods to assess impact and account for social value. Further research is needed to understand the implications of this in practice, and to understand how the results of the two methods could be used by decision-makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The results reveal that the analysis of some quality of life domains provides appropriate evidence to represent the emotional value generated by these organizations, and offers a holistic and understandable view of the individual's well-being, as Van Loon et al (2013) already suggested. In comparison with an emotional value measuring system based on global perceptions of consumer in their market transactions, as might be expected in a commercial company (Lazkano and Beraza, 2019;Ruiz-Roqueñi, 2020), our results show that, in disability organizations emotional value is related to personal well-being and collective values, and goes beyond the mere state of the individual's health or the coverage of their basic needs (Ashton et al, 2020;.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…The results reveal that the analysis of some quality of life domains provides appropriate evidence to represent the emotional value generated by these organizations, and offers a holistic and understandable view of the individual's well-being, as Van Loon et al (2013) already suggested. In comparison with an emotional value measuring system based on global perceptions of consumer in their market transactions, as might be expected in a commercial company (Lazkano and Beraza, 2019;Ruiz-Roqueñi, 2020), our results show that, in disability organizations emotional value is related to personal well-being and collective values, and goes beyond the mere state of the individual's health or the coverage of their basic needs (Ashton et al, 2020;.…”
Section: Discussionmentioning
confidence: 49%
“…Corvo et al (2021) conclude that of the 98 impact assessment models identified in the literature, SROI is the most widely used compared to other models coming from performance and management systems. Furthermore, the SROI methodology has emerged as a preferred technique for measuring social value and impact in the field of health and care services (Krlev et al, 2013), since some organizations such as the UK Department of Health have been promoting its application in social accounting for more than a decade (Millar and Hall, 2013;Banke-Thomas et al, 2015;Ashton et al, 2020;Corvo et al, 2021). However, this is not surprising since we collected the analyzed reports from the Social Value UK database, which could lead to a biased result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations